Homeschooling Policy and Practitioners’ Criticism in Indonesia - Dhian Sintapertiwi (IJELR: International Journal of Education, Language, and Religion, 2022)
Homeschooling in Indonesia is included as informal education. Unfortunately, many people still misunderstand the essence of homeschooling. It is often mistaken for non-formal education, conducted under the name of institutions. Homeschooling in this study only focuses on parents who directly educate their children at home. This qualitative study aims to reveal how the legal umbrellas that theoretically regulate homeschooling are based on the responses of four participants as practitioners in Indonesia. Constitution No. 20 in 2003 and Regulation of the Minister of Education and Culture (Permendikbud) No. 129 in 2014 are written evidence regarding the legality of homeschooling. This study found that collaborative homeschooling is the most doable choice for the participants, some community learning activities centers in certain areas tend to complicate the procedures for registration as well as equivalence examination, and the participants’ dilemma whether or not the government’s attention is needed for homeschooling in the future.